Structural behavior of stiffened steel silos subject to eccentric discharge pressures - Sun, Weiwei; Qi, Fu; Yuan, Jun; Cao, Yong; Wang, Lei; Zhou, Lijian; Wu, Yuqing; Feng, Jun (Journal of stored products research, 2025)
Thin-walled cylindrical steel silos are extensively used in many industries and agricultural sectors for storing materials. Eccentric discharge is widely recognized as the most severe load case for steel silos. Accordingly, this paper aims to present the results of a finite element analysis of the buckling strength of stiffened cylindrical silos during eccentric discharge under different pressure distribution proposals. The distribution patterns of Eurocode may lead to the lowest buckling loads. Subsequently, an extensive parametric analysis is carried out to verify the influence of various factors on the buckling behavior of the stiffened silo under eccentric discharge. Ultimately, based on the buckling stress design method of Eurocode, combined with parametric and regression analyses, the simple formula for calculating the stiffened steel silo buckling resistance is proposed. •Buckling analysis of steel silos with ring and vertical stiffeners under eccentric discharge conditions.•Assessment of the effects of varying eccentric discharge pressures on the buckling behaviour of steel silos.•Identification of key sensitivity parameters affecting buckling loads through parametric analysis.•Proposal of an advanced calculation method for axial ultimate strength based on parametric and regression analyses.